Vibration control with piezoelectric elements: The indirect measurement of the modal capacitance and coupling factor. (April 2021) - Berardengo, M.; Manzoni, S.; Høgsberg, J.; Vanali, M.
Highlights: Inexpensive methods for the indirect measurement of piezoelectric modal capacitance. The methods use the piezoelectric shunt with an L impedance or a negative capacitance. The methods rely on the estimates of system eigenfrequencies. A method also allows for estimating the coupling factor with reduced uncertainty. It provides reliable results also in case of small modal coupling factor. Abstract: The knowledge of the modal capacitance and electro-mechanical coupling factor is essential for a proper design of systems with embedded piezoelectric transducers and materials. In light of this, this paper presents two indirect methods for measuring the piezoelectric modal capacitance and a method to estimate the modal electro-mechanical coupling factor. All methods rely on simple vibration measurements of the structure with the piezoelectric transducer connected to a proper shunt impedance, thus avoiding measurements of piezoelectric current and voltage by expensive equipment. For the modal electro-mechanical coupling factor, the proposed method guarantees reduced uncertainty compared to traditional experimental estimation procedures. Upon introduction of the underlying theory, the paper experimentally demonstrates the reliability and effectiveness of the methods by comparison with well-established procedures.